DISCOURSE-ORIENTED LEARNING DALAM PENGAJARAN CONDITIONAL SENTENCE SEBAGAI ASPEK MEMAHAMI INSTRUKSI KERJA PADA PENDIDIKAN TEKNIK PENERBANGAN - Benny Kurnianto (Politeknik Penerbangan Indonesia Curug, 2019)
Teacher and student of English as a second or foreign language (ESL/EFL) feel quite difficult to understand conditional sentence in learning process. Therefore, there is necessity to change the method or technique in teaching this subject. This study attempts to analyse alternative method on teaching conditional sentence called as discourseoriented teaching. Therefore, it was suitable in this study to use discourse analysis which deal with context of an utterance. The case was a teaching learning process in class of aircraft maintenance program which concern on giving and understanding English verbal instruction on their career. This study found that discourse-oriented teaching could be an alternative method on teaching conditional sentence. It may require a great effort for the teacher to give contextual explanation for each type of conditional sentence, but it is effective for student to understand the usage of each type of conditional sentence in workplace.